Effect of Organic Acids on Salmonella Typhimurium Infection in Broiler Chickens - Menconi, A.; Reginatto, A.R.; Londero, A.; Pumford, N.R.; Morgan, M.; Hargis, B.M.; Tellez , G. (International Journal of Poultry Science, 2013)
An alternative to antibiotics is the use of certain organic acids for routinely encountered pathogens in the poultry industry. Direct acidification of drinking water with organic acids could significantly reduce the amount of recoverable Salmonella Typhimurium (ST) from the crop and cecal tonsils when used during the pre-slaughter feed withdrawal period. In the present study, in vitro and in vivo evaluations were conducted to compare a commercially available water acidifier (Optimizer®), versus two formulations of organic acid mix (OAM), made up of of acetic, citric and propionic acids at a final concentration of either 0.031% or 0.062%, to reduce Salmonella Typhimurium in the crop and cecal tonsils of broiler chicks during a 24 h period. The two OAM showed better in vitro activity to reduce Salmonella when compared to control. In vivo, the OAM (0.062%) had a similar effect as Optimizer® showing a significant reduction in total number of ST positive cecal tonsils, and reducing the number of ST in the crop when compared with controls (P < 0.05). All treatments reduced the number of ST recovered from crop contents at 24 h. This new formulation of OAM has great potential as a crop sanitizer and will be further evaluated under conditions similar to commercial chickens.